The impact of top-down and bottom-up listening strategies on the students’ listening comprehension: case of Intermediate Intensive English II students of the Department of Foreign Languages, University of El Salvador - Cañas Vides, Stephanie Ivonne
Learning English as a foreign language is not an easy process, and Spanish native speakers have their issues during the process. Clearly, it may take time to master a language where students need to organize their knowledge into appropriate coherent structures, to be able to express a message, language is compound of four skills; listening, speaking, reading and writing. In any language listening is the first skill that a native speaker develops; if this is assumed, then it can be said that listening is the first skill that learners face in their learning or acquisition process. Krashen (1985) argues that people acquire language by understanding the linguistic information they hear. Knowing this, it can be assumed that listening is the base of language. First, children listen to a lot of words and phrases given by their parents or people around them, and then after they have internalized a big number of words they begin the process of speaking. In many EFL classrooms listening has attracted the least attention of the four skills. This study sought to show the importance of listening strategies instruction. To carry out this study the researchers applied top down and bottom-up listening strategies to one group of students in order to provide the learners the listening input to develop this skill.